The vaginal microbiome in uterine transplantation. (8th August 2019) - Jones, BP; Saso, S; L'Heveder, A; Bracewell‐Milnes, T; Thum, M‐Y; Diaz‐Garcia, C; MacIntyre, DA; Quiroga, I; Ghaem‐Maghami, S; Testa, G; Johannesson, L; Bennett, PR; et al.
Abstract : Women with congenital absolute uterine factor infertility (AUFI) often need vaginal restoration to optimise sexual function. Given their lack of procreative ability, little consideration has previously been given to the resultant vaginal microbiome (VM). Uterine transplantation (UTx) now offers the opportunity to restore these women's reproductive potential. The structure of the VM is associated with clinical and reproductive implications that are intricately intertwined with the process of UTx. Consideration of how vaginal restoration methods impact VM is now warranted and assessment of the VM in future UTx procedures is essential to understand the interrelation of the VM and clinical and reproductive outcomes. Tweetable abstract: The vaginal microbiome has numerous implications for clinical and reproductive outcomes in the context of uterine transplantation. Tweetable abstract: The vaginal microbiome has numerous implications for clinical and reproductive outcomes in the context of uterine transplantation.